The Influence of Inquiry Approach to The Physics Learning Outcomes in Senior High School 9 Makassar - Syamsul Wahid* (Journal of Physics Education : Review and Research, 2024)
This research was done to know: (1) The physics learning outcomes of students at class in senior high school 9 Makassar that taught by inquiry learning. (2) The physics learning outcomes of students at class in senior high school 9 Makassar that taught by conventional teaching. (3) The differences of physics learning outcomes in senior high school 9 Makassar between the students that taught by inquiry learning approach and the students that taught by conventional teaching. This research is a real experiment that uses Posttest Only Control Design. The population in this research is students at class in Senior High School 9 Makassar. Based on the descriptive analysis showed that the average score of physics learning outcomes of students that taught using inquiry learning is 27.03 and its deviation standard is 3.32 while the average score of physics learning outcome that taught without inquiry learning approach is 25.62 and its deviation standard is 3.28. The results of inferential analysis showed that there is a difference between physics learning outcomse of students that taught by inquiry learning approach and the students that taught without inquiry learning approach with the real level α = 0.05